Two-phase flow metering of heavy oil with Coriolis Mass Flow Metering: formal trials at NEL - Henry, M; Tombs, M; Zhou, F (Flow Measurement Institute, 2016)
A talk on the different ways of measuring and metering the flow of liquids and recent developments in this field